P-012 Rates of complications of embolising intracranial aneurysms over time: Do we continue to improve with experience?. (26th July 2014) - Crimmins, M; Banihashemi, A; Gobin, P
Abstract : Introduction: In this study our aim was to assess the change in complication rates for endovascular coil embolization of intracranial aneurysms over the course of our interventional neuroradiologists' careers. Methods: Data was collected on all intracranial aneurysm embolization procedures performed were retrieved from a retrospectively maintained database. All intraoperative complications were gathered. They were categorized into: 1. major complications (consisting of haemorrhagic and thromboembolic events) and 2. Non-major and technical complications (such as stent and coil migration and coil breakage). Time was divided into 3 months increments (quarters) from the date an attending started work as an interventional neuroradiology Attending. The data was visualised as percentage of complications over time (Figure 1 ). Results: The complication rate for major complication at 1, 3, 5, 10, 15 years was: 5.0%, 6.8%, 7.0%, 6.0% and 5.25% respectively. All complications (Major, non-major and technical) at 1, 3, 5, 10 and 15 years were 9.2%, 9.4%, 9.3%, 8.4% and 7.0% respectively. Complications rates were higher in the first 30 months of an interventionalist attending's career and decreased thereafter. Conclusion: There was a gradual drop in complication rates with experience long after an attending has completed fellowship training. This complication rate seems to level off after about 6 years of training, which was longer than the authors expected. Disclosures: M. Crimmins: None. A. Banihashemi: None. P. Gobin: None.